A Review: Antibacterial Activity of Metal Impregnated Zeolite in Water Treatment Process - Sutianingsih, Yulis; K., Widya Ernayati; Kurniawan, Teguh (Jurnal Kartika Kimia, 2022)
Environmental and health problems related to water pollution by bacteria are a big challenge in the water treatment process. This pollution is caused by industrial development and increased population growth. Bacterial removal methods in water are continuously developed to find an efficient water treatment process. Zeolite has the potential to be an adsorbent used in the water treatment process. Zeolite has been widely used in adsorption and catalytic processes. Zeolite is a porous alumina silicate consisting of silicon, aluminium, and oxygen in its framework. Zeolite cations can be exchanged with monovalent or divalent ions. Zeolite does not have antibacterial activity, so it should combine with metal cations such as Ag, Cu, Zn, and Fe. Metal active that loaded into zeolite framework is a solution to improve the zeolite performance for bacteries removing in water. The impregnation method is the most widely used for the metal loading process into zeolite framework, because of its simple and economical process. This review will discuss natural and synthetic zeolites, types of metal, impregnation process, the antibacterial activity of metal impregnated zeolite, bacterial attack mechanism, and antibacterial application of metal impregnated zeolite in water